2006
DOI: 10.1002/jmv.20673
|View full text |Cite
|
Sign up to set email alerts
|

Determination of HPV type 16 and 18 viral load in cervical smears of women referred to colposcopy

Abstract: It has been recognized that human papillomavirus infection is the major causal factor for high-grade cervical lesions. The aim of the study was to evaluate the relationship between HPV 16 and 18 viral loads and cervical status in different age strata. A duplex real time PCR method was devised to determine HPV 16 and 18 viral load per million of human cells using an in house plasmidic construct as a standard of quantification. The 151 cervical scrapes were collected before colposcopic examination from either ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
56
0
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 34 publications
(26 reference statements)
4
56
0
6
Order By: Relevance
“…Many previous studies have found a positive association between viral load and disease severity, which has led to the idea of using viral load as a biomarker to determine the status of cervical disease or to predict its progression (4,11,13,19,23,24,28,30,31). However, at the same time, contradictory data have also been generated (1,15,26,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies have found a positive association between viral load and disease severity, which has led to the idea of using viral load as a biomarker to determine the status of cervical disease or to predict its progression (4,11,13,19,23,24,28,30,31). However, at the same time, contradictory data have also been generated (1,15,26,34).…”
Section: Discussionmentioning
confidence: 99%
“…As the disease worsens, the virus becomes integrated, which is a genome form not capable of self-replicating, and therefore the mechanism for maintaining a high viral load is uncertain. Many studies that attempted to examine viral load associations did not analyze the physical status of the viral genome (4,12,13,18,28,29). In addition, some studies have used a method that measured the total viral load of a mixture of HPV types (13,18,28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Its composition (chimeric preparation of HPV18 and human albumin targets) was designed such that it would not interfere with any of the organisms found in stool specimens. A chimeric nucleotide fragment was constructed as previously described for quantification of the IS6110 gene copy number (Carcopino et al, 2006;Menard et al, 2008) (Fig. 2).…”
mentioning
confidence: 99%
“…El análisis de la carga viral se realizó mediante PCR cuantitativa, se observó un amplio rango de valores en LIEBG y LIEAG, inclusive en el grupo sin lesión se observaron valores altos en ocho casos, estos valores altos en mujeres sin lesión son probablemente el reflejo de una infección productiva con mayor riesgo de progresar a LEIBG, dada la asociación observada en este y otros estudios (Carcopino et al, 2006;Flores et al, 2006;Cricca et al, 2007;Saunier et al, 2008;Shukla et al, 2014) entre mayor valor de carga viral y progresión de la enfermedad. Al comparar las medias de carga viral en cada grupo histológico se observó una diferencia estadísticamente significativa, con un incremento a mayor severidad de la enfermedad.…”
Section: Discussionunclassified
“…Al comparar las medias de carga viral en cada grupo histológico se observó una diferencia estadísticamente significativa, con un incremento a mayor severidad de la enfermedad. Los estudios en los que se ha empleado la PCR cuantitativa para evaluar la carga viral han mostrado de manera consistente que a mayor grado de la lesión es significativamente mayor la carga viral (Carcopino et al, 2006;Flores et al, 2006;Cricca et al, 2007;Saunier et al, 2008;Shukla et al, 2014), aunque en algunos estudios no se ha encontrado esta diferencia (Andersson et al, 2005;Briolat et al, 2007;Boulet et al, 2009). Cabe señalar que una comparación directa entre nuestros resultados y los obtenidos previamente por otros grupos es difícil dadas las diferencias en las técnicas de tiempo real empleadas (Taqman, SYBR Green), y las múltiples formas de presentación de los resultados (copias/ célula, copias/ng de ADN, copias/muestra).…”
Section: Discussionunclassified